AI and the Transformation of Global Politics (International Journal of Scientific Research and Management (IJSRM), 2025)
The Fourth Industrial Revolution has profound impacts on the development and transformation of different aspects in society, one of which is the emergence of AI (artificial intelligence). In the context the global political situation is marked by complex challenges and shifting dynamics, reflecting the interconnected nature of contemporary issues such as geopolitical tensions, economic fragmentation and emerging threat, AI has significantly shaped global politics by revolutionizing decision-making, security, and economic competition. It empowers nations with advanced tools for diplomacy, cybersecurity, and predictive analytics, enhancing their strategic influence on the world stage. The emergence of AI technology has ushered in a new age in global security, defenses, political economics to political systems. The paper examines how AI has been incorporated into these fields in different contexts, such as autonomous weapon systems, surveillance, decision - making processes and economic changes and analyze complex interactions between AI and politics and society issues in reshaping global politics and international orders.